'Australia in this Matter is under Some Scrutiny': Early Australian Initiatives to the Rhodesian Problem, 1961–64. Issue 1 (2nd January 2020) - Jordan, Matthew
Abstract: Australia's attitude towards the problem of Rhodesian independence in the early 1960s has been largely ignored by the literature on the subject. Not unnaturally, the focus of recent research and scholarship has been Australia's response to Rhodesia's Unilateral Declaration of Independence (UDI) in November 1965 and the absence of any appetite for sanctions against the white minority regime. This lack of enthusiasm is often interpreted as symptomatic of an abiding sympathy not only for 'kith and kin' but also for Rhodesia's white supremacist policies, which are invariably conflated with Australia's own racially discriminatory practices. While senior Australian policymakers were uncomfortable with the notion of alienating people with whom they shared traditional political, economic and sentimental ties, they showed no support for the perpetual domination of the African population by Europeans, and indeed, accepted both the desirability and inevitability of black majority government. With this in mind, they worked hard to contribute to a genuine solution to the Rhodesian problem in the early 1960s and were deeply critical of Britain for refusing to adopt positive action. Although Australian Prime Minister Robert Menzies continued to struggle with these competing forces, he too recognised the irresistible nature of black rule and acted accordingly.